RADIOLOGICAL AGE ESTIMATION FROM EPIPHYSEAL UNION OF BASE OF FIRST METACARPAL, RADIUS AND ULNA (Journal of Forensic Medicine & Toxicology, 2016)
The diaphyseo epiphyseal union is universally present in all individuals and therefore may be taken as a legally acceptable indicator of age. The assessment of age for legal purpose is of considerable importance for administration of justice. The universally accepted methods of estimation of age in living person are 1) physical development and secondary sexual characteristics 2) clinical examination of teeth for eruption of teeth and calcification of root of third molar by radiological examination 3) radiological examination of diaphyseo epiphyseal union of long bones. The union of diaphyseo epiphyseal of 1st metacarpal has been studied in 120 candidates (60 males and 60 females). The results were also compared with union of lower end of radius and ulna in these 120 candidates. The complete diaphyseo epiphyseal union at the base of Metacarpal was observed in the age group of 16 - 17 years in both the sexes. The complete diaphyseo epiphyseal union at the lower end of radius and Ulna was observed in the age group of 18 - 19 years in both the sexes.
Keywords: Age estimation; 1st metacarpal; radius; ulna; Radiological study